Alternative genomic diagnoses for individuals with a clinical diagnosis of Dubowitz syndrome. - Dyment, David A; O'Donnell-Luria, Anne; Agrawal, Pankaj B; Coban Akdemir, Zeynep; Aleck, Kyrieckos A; Antaki, Danny; Al Sharhan, Hind; Au, Ping-Yee B; Aydin, Hatip; Beggs, Alan H; Bilguvar, Kaya; Boerwinkle, Eric; et al. (Am J Med Genet A, 2021)
Dubowitz syndrome (DubS) is considered a recognizable syndrome characterized by a distinctive facial appearance and deficits in growth and development. There have been over 200 individuals reported with Dubowitz or a "Dubowitz-like" condition, although no single gene has been implicated as responsible for its cause. We have performed exome (ES) or genome sequencing (GS) for 31 individuals clinically diagnosed with DubS. After genome-wide sequencing, rare variant filtering and computational and Mendelian genomic analyses, a presumptive molecular diagnosis was made in 13/27 (48%) families. The molecular diagnoses included biallelic variants in SKIV2L, SLC35C1, BRCA1, NSUN2; de novo variants in ARID1B, ARID1A, CREBBP, POGZ, TAF1, HDAC8, and copy-number variation at1p36.11(ARID1A), 8q22.2(VPS13B), Xp22, and Xq13(HDAC8). Variants of unknown significance in known disease genes, and also in genes of uncertain significance, were observed in 7/27 (26%) additional families. Only one gene, HDAC8, could explain the phenotype in more than one family (N = 2). All but two of the genomic diagnoses were for genes discovered, or for conditions recognized, since the introduction of next-generation sequencing. Overall, the DubS-like clinical phenotype is associated with extensive locus heterogeneity and the molecular diagnoses made are for emerging clinical conditions sharing characteristic features that overlap the DubS phenotype.

Biallelic variants in HPDL, encoding 4-hydroxyphenylpyruvate dioxygenase-like protein, lead to an infantile neurodegenerative condition. - Ghosh, Shereen G; Lee, Sangmoon; Fabunan, Rudy; Chai, Guoliang; Zaki, MAH S; Abdel-Salam, Ghada; Sultan, Tipu; Ben-Omran, Tawfeg; Alvi, Javeria Raza; McEvoy-Venneri, Jennifer; Stanley, Valentina; Patel, Aakash; et al. (Genet Med, 2021)
PURPOSE: Dioxygenases are oxidoreductase enzymes with roles in metabolic pathways necessary for aerobic life. 4-hydroxyphenylpyruvate dioxygenase-like protein (HPDL), encoded by HPDL, is an orphan paralogue of 4-hydroxyphenylpyruvate dioxygenase (HPD), an iron-dependent dioxygenase involved in tyrosine catabolism. The function and association of HPDL with human diseases remain unknown. METHODS: We applied exome sequencing in a cohort of over 10,000 individuals with neurodevelopmental diseases. Effects of HPDL loss were investigated in vitro and in vivo, and through mass spectrometry analysis. Evolutionary analysis was performed to investigate the potential functional separation of HPDL from HPD. RESULTS: We identified biallelic variants in HPDL in eight families displaying recessive inheritance. Knockout mice closely phenocopied humans and showed evidence of apoptosis in multiple cellular lineages within the cerebral cortex. HPDL is a single-exonic gene that likely arose from a retrotransposition event at the base of the tetrapod lineage, and unlike HPD, HPDL is mitochondria-localized. Metabolic profiling of HPDL mutant cells and mice showed no evidence of altered tyrosine metabolites, but rather notable accumulations in other metabolic pathways. CONCLUSION: The mitochondrial localization, along with its disrupted metabolic profile, suggests HPDL loss in humans links to a unique neurometabolic mitochondrial infantile neurodegenerative condition.
Keywords: 4-Hydroxyphenylpyruvate Dioxygenase; Animals; Dioxygenases; Exons; Mice; Mice, Knockout; Phenotype

Molecular diagnosis in recessive pediatric neurogenetic disease can help reduce disease recurrence in families. - Issa, Mahmoud Y; Chechlacz, Zinayida; Stanley, Valentina; George, Renee D; McEvoy-Venneri, Jennifer; Belandres, Denice; Elbendary, Hasnaa M; Gaber, Khaled R; Nabil, Ahmed; Abdel-Hamid, Mohamed S; Zaki, MAH S; Gleeson, Joseph G (BMC Med Genomics, 2020)
BACKGROUND: The causes for thousands of individually rare recessive diseases have been discovered since the adoption of next generation sequencing (NGS). Following the molecular diagnosis in older children in a family, parents could use this information to opt for fetal genotyping in subsequent pregnancies, which could inform decisions about elective termination of pregnancy. The use of NGS diagnostic sequencing in families has not been demonstrated to yield benefit in subsequent pregnancies to reduce recurrence. Here we evaluated whether genetic diagnosis in older children in families supports reduction in recurrence of recessive neurogenetic disease. METHODS: Retrospective study involving families with a child with a recessive pediatric brain disease (rPBD) that underwent NGS-based molecular diagnosis. Prenatal molecular testing was offered to couples in which a molecular diagnosis was made, to help couples seeking to prevent recurrence. With this information, families made decisions about elective termination. Pregnancies that were carried to term were assessed for the health of child and mother, and compared with historic recurrence risk of recessive disease. RESULTS: Between 2010 and 2016, 1172 families presented with a child a likely rPBD, 526 families received a molecular diagnosis, 91 families returned to the clinic with 101 subsequent pregnancies, and 84 opted for fetal genotyping. Sixty tested negative for recurrence for the biallelic mutation in the fetus, and all, except for one spontaneous abortion, carried to term, and were unaffected at follow-up. Of 24 that genotyped positive for the biallelic mutation, 16 were electively terminated, and 8 were carried to term and showed features of disease similar to that of the older affected sibling(s). Among the 101 pregnancies, disease recurrence in living offspring deviated from the expected 25% to the observed 12% ([95% CI 0·04 to 0·20], p = 0·011). CONCLUSIONS: Molecular diagnosis in an older child, coupled with prenatal fetal genotyping in subsequent pregnancies and genetic counselling, allows families to make informed decisions to reduce recessive neurogenetic disease recurrence.
Keywords: Child, Preschool; Female; Genes, Recessive; Genetic Markers; Genetic Predisposition to Disease; Genetic Testing; Genotype; High-Throughput Nucleotide Sequencing; Humans; Infant; Infant, Newborn; Male; Mutation; Nervous System Diseases; Pedigree; Pregnancy; Prenatal Diagnosis; Recurrence; Retrospective Studies

Biallelic variants in KIF14 cause intellectual disability with microcephaly. - Makrythanasis, Periklis; Maroofian, Reza; Stray-Pedersen, Asbjørg; Musaev, Damir; Zaki, Maha S; Mahmoud, Iman G; Selim, Laila; Elbadawy, Amera; Jhangiani, Shalini N; Coban Akdemir, Zeynep H; Gambin, Tomasz; Sorte, Hanne S; et al. (Eur J Hum Genet, 2018)
Kinesin proteins are critical for various cellular functions such as intracellular transport and cell division, and many members of the family have been linked to monogenic disorders and cancer. We report eight individuals with intellectual disability and microcephaly from four unrelated families with parental consanguinity. In the affected individuals of each family, homozygosity for likely pathogenic variants in KIF14 were detected; two loss-of-function (p.Asn83Ilefs*3 and p.Ser1478fs), and two missense substitutions (p.Ser841Phe and p.Gly459Arg). KIF14 is a mitotic motor protein that is required for spindle localization of the mitotic citron rho-interacting kinase, CIT, also mutated in microcephaly. Our results demonstrate the involvement of KIF14 in development and reveal a wide phenotypic variability ranging from fetal lethality to moderate developmental delay and microcephaly.
Keywords: Child; Child, Preschool; Female; Humans; Intellectual Disability; Kinesin; Loss of Function Mutation; Microcephaly; Mutation, Missense; Oncogene Proteins; Pedigree; Phenotype; Protein Domains; Syndrome

Genetic variants in components of the NALCN-UNC80-UNC79 ion channel complex cause a broad clinical phenotype (NALCN channelopathies). - Bramswig, Nuria C; Bertoli-Avella, Aida M; Albrecht, Beate; Al Aqeel, Aida I; Alhashem, Amal; Al-Sannaa, Nouriya; Bah, Maissa; Bröhl, Katharina; Depienne, Christel; Dorison, Nathalie; Doummar, Diane; Ehmke, Nadja; et al. (Hum Genet, 2018)
NALCN is a conserved cation channel, which conducts a permanent sodium leak current and regulates resting membrane potential and neuronal excitability. It is part of a large ion channel complex, the "NALCN channelosome", consisting of multiple proteins including UNC80 and UNC79. The predominant neuronal expression pattern and its function suggest an important role in neuronal function and disease. So far, biallelic NALCN and UNC80 variants have been described in a small number of individuals leading to infantile hypotonia, psychomotor retardation, and characteristic facies 1 (IHPRF1, OMIM 615419) and 2 (IHPRF2, OMIM 616801), respectively. Heterozygous de novo NALCN missense variants in the S5/S6 pore-forming segments lead to congenital contractures of the limbs and face, hypotonia, and developmental delay (CLIFAHDD, OMIM 616266) with some clinical overlap. In this study, we present detailed clinical information of 16 novel individuals with biallelic NALCN variants, 1 individual with a heterozygous de novo NALCN missense variant and an interesting clinical phenotype without contractures, and 12 individuals with biallelic UNC80 variants. We report for the first time a missense NALCN variant located in the predicted S6 pore-forming unit inherited in an autosomal-recessive manner leading to mild IHPRF1. We show evidence of clinical variability, especially among IHPRF1-affected individuals, and discuss differences between the IHPRF1- and IHPRF2 phenotypes. In summary, we provide a comprehensive overview of IHPRF1 and IHPRF2 phenotypes based on the largest cohort of individuals reported so far and provide additional insights into the clinical phenotypes of these neurodevelopmental diseases to help improve counseling of affected families.
Keywords: Adolescent; Adult; Carrier Proteins; Channelopathies; Child; Child, Preschool; Developmental Disabilities; Female; Genetic Markers; Genetic Variation; Humans; Infant; Infant, Newborn; Male; Membrane Proteins; Phenotype; Sodium Channels; Young Adult

Loss of Protocadherin-12 Leads to Diencephalic-Mesencephalic Junction Dysplasia Syndrome. - Guemez-Gamboa, Alicia; Çağlayan, Ahmet Okay; Stanley, Valentina; Gregor, Anne; Zaki, Maha S; Saleem, Sahar N; Musaev, Damir; McEvoy-Venneri, Jennifer; Belandres, Denice; Akizu, Naiara; Silhavy, Jennifer L; Schroth, Jana; et al. (Ann Neurol, 2018)
OBJECTIVE: To identify causes of the autosomal-recessive malformation, diencephalic-mesencephalic junction dysplasia (DMJD) syndrome. METHODS: Eight families with DMJD were studied by whole-exome or targeted sequencing, with detailed clinical and radiological characterization. Patient-derived induced pluripotent stem cells were derived into neural precursor and endothelial cells to study gene expression. RESULTS: All patients showed biallelic mutations in the nonclustered protocadherin-12 (PCDH12) gene. The characteristic clinical presentation included progressive microcephaly, craniofacial dysmorphism, psychomotor disability, epilepsy, and axial hypotonia with variable appendicular spasticity. Brain imaging showed brainstem malformations and with frequent thinned corpus callosum with punctate brain calcifications, reflecting expression of PCDH12 in neural and endothelial cells. These cells showed lack of PCDH12 expression and impaired neurite outgrowth. INTERPRETATION: DMJD patients have biallelic mutations in PCDH12 and lack of protein expression. These patients present with characteristic microcephaly and abnormalities of white matter tracts. Such pathogenic variants predict a poor outcome as a result of brainstem malformation and evidence of white matter tract defects, and should be added to the phenotypic spectrum associated with PCDH12-related conditions. Ann Neurol 2018;84:646-655.